Upaya Meningkatan Minat Generasi Muda Dalam Kegiatan Rebana Di Desa Teluk Batil - Ramadani, Novira; Nurhayati, Nurhayati; Sari, Ruszita (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
In the 21st century, without realizing it, traditional art gradually eroded and began to fall out of favor. Many teenagers or the younger generation prefer modern arts such as western pop, Korean pop and many more. The purpose of this study is to clearly describe efforts to increase young women's interest in tambourine activities in Teluk Batil Village. This research is a type of qualitative research (Qualitative Research) which is descriptive in nature. Based on the results of interviews and observations at the house of the head of the tambourine Harapan Bunda in Teluk Batil village, it can be concluded that only a few teenagers in Teluk Batil are interested in participating in tambourine activities and it can be said that the interest of teenagers is still low in this tambourine activity, because they consider tambourines to be out of trend. again and a bit old-fashioned, as well as globalization which makes sophisticated technology such as tiktok, instagram, twitter and so on. The forms of efforts that can be made are: 1) Motivation, 2) Support, and 3) Outreach